Automobile electrical and electronic systems - Denton, Tom (Abingdon Routledge, 2018)
This textbook will help you learn all the skills you need to pass all Vehicle Electrical and Electronic Systems courses and qualifications.
Keywords: Công nghệ kỹ thuật ô tô